One‐Way Particle Transport Using Oscillatory Flow in Asymmetric Traps. Issue 9 (29th January 2018) - Lee, Jaesung; Burns, Mark A.
Abstract: One challenge of integrating of passive, microparticles manipulation techniques into multifunctional microfluidic devices is coupling the continuous‐flow format of most systems with the often batch‐type operation of particle separation systems. Here, a passive fluidic technique—one‐way particle transport—that can conduct microparticle operations in a closed fluidic circuit is presented. Exploiting pass/capture interactions between microparticles and asymmetric traps, this technique accomplishes a net displacement of particles in an oscillatory flow field. One‐way particle transport is achieved through four kinds of trap–particle interactions: mechanical capture of the particle, asymmetric interactions between the trap and the particle, physical collision of the particle with an obstacle, and lateral shift of the particle into a particle–trapping stream. The critical dimensions for those four conditions are found by numerically solving analytical mass balance equations formulated using the characteristics of the flow field in periodic obstacle arrays. Visual observation of experimental trap–particle dynamics in low Reynolds number flow (<0.01) confirms the validity of the theoretical predictions. This technique can transport hundreds of microparticles across trap rows in only a few fluid oscillations (<500 ms per oscillation) and separate particles by their size differences. Abstract : Passive fluidic particle transport using asymmetric traps in nonacoustic oscillatory flow is developed. The conditions to achieve this technique are based on the mass balance of fluid flows, the theory of deterministic lateral displacement of microparticles, and experimental validation. This technique can transport or separate microparticles in a closed chamber and facilitate the integration of the microparticle system into portable lab‐on‐a‐chip devices.